(untitled) (Undergraduate Conference on Applied Linguistics, Linguistics, and Literature, 2022)
This study is based on a study that attempted to describe students’ perception of the online teaching-learning process. The main purpose of the study was to determine students’ perceptions of the implementation of online learning as seen through interactivity, independence, accessibility, and enrichment. This study used the descriptive qualitative method. The population was one hundred eighty in class eleven-grade, and the sample was thirty-six students in class eleven-grade. The writers used a questionnaire in Google Form to collect data. The questionnaires are twenty-four questions and it was used close-ended questions on a scale of 1-5. The writers found that students’ perceptions toward the online teaching-learning process are as follows: 32% answered agreed with interactivity, 39% agreed with independence, 42% agreed with accessibility, and 38% were neutral on enrichment. It can be concluded that online learning can support the teaching–learning process. Although in online learning, students have problems such as lack of confidence, lack of discipline, and also require a large quota.